The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1051/matecconf/201818803009
|View full text |Cite
|
Sign up to set email alerts
|

The size effect of rebars, on the structural integrity of reinforced concrete structures, which are exposed to corrosive environments

Abstract: Abstract. The goal of the present study is to mention the importance of underestimation of the corrosion damage developed in critical load bearing areas, on the column bases, where formation of plastic hinges is attended, mainly during strong seismic events (Figure 1). In such cases, plastic hinges are expected to absorb the seismic energy, owed to seismic vibration. However, chloride induced corrosion is responsible for significant degradation of concrete infrastructures located in coastal areas. Forecasting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
(17 reference statements)
2
2
0
Order By: Relevance
“…More specific, the differential aeration corrosion refers to each specimen, when different parts of which are exposed to different concentrations of oxygen. In that sense, as already demonstrated in previous work of the authors [26,27], specimens with a shorter exposed length showed greater mass loss in comparison with specimens of the same total length but with longer exposed length, as the corrosion phenomena were bounded to a smaller area. In that manner, the parameter of exposed length affects not only the corrosion rate (percentage mass loss) but also the surface damage of corroded steel bars.…”
Section: Results -Discussionsupporting
confidence: 82%
“…More specific, the differential aeration corrosion refers to each specimen, when different parts of which are exposed to different concentrations of oxygen. In that sense, as already demonstrated in previous work of the authors [26,27], specimens with a shorter exposed length showed greater mass loss in comparison with specimens of the same total length but with longer exposed length, as the corrosion phenomena were bounded to a smaller area. In that manner, the parameter of exposed length affects not only the corrosion rate (percentage mass loss) but also the surface damage of corroded steel bars.…”
Section: Results -Discussionsupporting
confidence: 82%
“…In a similar way, as already demonstrated in the previous work of the authors [48,58], specimens with a shorter exposed length showed greater mass loss in comparison with specimens of the same total length but with longer exposed length, as the corrosion phenomenon was limited to a smaller area. Similar to the above mentioned, in the present manuscript, tensile specimens, wherein the parts with an oxygen deficit were larger than those of the fatigue specimens, denoted a higher percentage of mass loss for both categories of steel reinforcement.…”
Section: Mass Losssupporting
confidence: 83%
“…Equivalent remarks triggered the prosecution of the present study. Specifically, searching in existing literature, the significance of the exposed length of the specimens, has rarely been reported Drakakaki and Apostolopoulos, 2018;. Taking into account a few findings in recent literature Drakakaki, and Apostolopoulos, 2018), it seems that the size of the exposedto the corrosive environmentarea of steel is of major importance for the evaluation of the damage level that has been incurred to the material.…”
Section: Ijsi 115mentioning
confidence: 99%
“…Specifically, searching in existing literature, the significance of the exposed length of the specimens, has rarely been reported Drakakaki and Apostolopoulos, 2018;. Taking into account a few findings in recent literature Drakakaki, and Apostolopoulos, 2018), it seems that the size of the exposedto the corrosive environmentarea of steel is of major importance for the evaluation of the damage level that has been incurred to the material. However, corrosion damage assessment, without taking into consideration the exposed and the unexposed lengths of steel reinforcement increases the risk for erroneous predictions concerning the mechanical behavior of steel reinforcement (Apostolopoulos et al, 2017;Imperatore et al, 2017).…”
Section: Ijsi 115mentioning
confidence: 99%